Nitrousoxide as a conscious sedative in minor oral surgical procedure - Rakesh Mohan; Vigil Dev Asir; Shanmugapriyan; Vijay Ebenezr; Abu Dakir; Balakrishnan; Jeffin Jacob (Wolters Kluwer Medknow Publications, 2015)
Nitrous oxide (N 2 O) is the most commonly used inhalation anesthetic in dentistry and is commonly used in emergency centers and ambulatory surgery centers as well. When used alone, it is incapable of producing general anesthesia reliably. However, as a single agent, it has an impressive safety and is excellent for providing minimal and moderate sedation for apprehensive minor oral surgical procedure. In this article, action of N 2 O in overcoming the anxiety and pain of the patient during the minor oral surgery and its advantages and disadvantages, have been reviewed.